Epitaxial iron silicides on Si(001): an investigation with scanning tunneling microscopy and spectroscopy - Raunau, Werner; Niehus, Horst; Comsa, George (Surface science letters, 1993)
Iron silicide films have been grown epitaxially on Si(001) by solid phase epitaxy (SPE) in UHV. The grown silicide films have been investigated in geometric and electronic structure with scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS). After deposition of small amounts of iron in the submonolayer range and annealing at 750 K iron silicide islands are formed which may be attributed to FeSi 2 with CaF 2 structure (γ-FeSi 2). Further annealing at 900 K leads to the formation of orthorhombic β-FeSi 2 with its (100) plane parallel to the substrate. β-FeSi 2(100) has been grown for initial coverages up to about 2 ML. STS shows that β-FeSi 2 films are semiconducting with a gap width E g ∼ 0.90 eV. Increasing the initial Fe coverage to 3 ML and annealing at 900 K changes the epitaxial relationship: not β-FeSi 2(100) but β-FeSi 2(001) is grown on the Si(001) substrate.